Mindenütt idegen . Aliens Everywhere - Katona, Zsuzsa; Nyeste, Péter (Aster Film, 2007)
Verzio FF submission Refugee children in Hungary whose only opportunity for a holiday is the yearly camp organized by Menedék, and NGO protecting the rights of refugees in Hungary.